Évaluation délibérative des effets des modes de gestion des aménagements hydroagricoles sur l’accès aux facteurs de production du riz dans la vallée du Niger au Bénin - Abdou Razak Maman; Janvier Egah; Mohamed Nasser Baco (VertigO)
The present study reveals the involvement of local stakeholders in assessing the impact of the form of natural resource management by putting them at the heart of the process. The methodological approach known as "citizen's jury", supported by four focus groups on hydro-agricultural developments in the Niger Valley, was explored in this study. The perimeters concerned are the Producer Union Groups for the Malanville Perimeter (UGPPM), the Sota perimeter and the lowlands developed in the villages of Garou and Toumboutou. Four categories of effects were analyzed: contextual effects, substantive effects, procedural effects and cognitive effects. The creativity revealed by this analytical model lies in its holistic nature and its ability to apprehend the effects induced by participatory approaches in four dimensions, taking into account the structural relationships between them. The four categories of effects analyzed have made it possible to understand that, in the field of natural resource governance around hydroagricultural developments, it is possible to engage in dialogue, to argue on the basis of different knowledge, experience and know-how, and that it is essential, for effective participation, to confront the different points of view through quality debates based on reasoning with the aim of finding a consensus.